OPTIMASI DOSIS PAC DAN FLOKULAN ANIONIK PADA PROSES KOAGULASI-FLOKULASI LIMBAH TEKSTIL DI IPAL POLITEKNIK STTT BANDUNG - - Sukirman; Wulan Safrihatini Atikah; Octianne Djamaludin; Eka Oktariani; Naufal Faris Wijaya (Politeknik STTT Bandung, 2026)
The Wastewater Treatment Plant (WWTP) at Politeknik STTT Bandung treats liquid waste using a coagulation-flocculation method with Poly Aluminium Chloride (PAC) and anionic flocculant; however, the optimum dosage of these chemicals has never been determined. This study aims to determine the optimum concentration of PAC and anionic flocculant and analyze the efficiency of pollutant removal and treatment costs. The jar test method was employed by varying the concentrations of PAC (100, 200, 300 mg/L) and anionic flocculant (0, 5, 10, 15 mg/L) on wastewater samples. The effectiveness of each treatment was analyzed based on the parameters of Total Solids (TS), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), color, and turbidity. The results showed that the optimum concentration was 200 mg/L of PAC and 5 mg/L of anionic flocculant. At this dosage, the removal efficiency achieved was very high for COD (95%), BOD (81%), TSS (81%), and turbidity (83%), and significant for TS (69%), and TDS (50%). The treatment cost required to achieve this efficiency is IDR 52,171 per cubic meter. It was concluded that the optimization of coagulant and flocculant dosages successfully and significantly improved liquid waste treatment performance at an efficient cost, thus it is recommended for application in the WWTP's operation.